2001
DOI: 10.1562/0031-8655(2001)074<0453:copaqt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photosensitizer (AlPcS2) Quantification Techniques: In Situ Fluorescence Microsampling Versus Tissue Chemical Extraction¶

Abstract: A noninvasive in situ fluorescence-based method for the quantification of the photosensitizer chloroaluminum disulfonated phthalocyanine was compared to the highly accurate but nonreal time ex vivo spectrofluorometry method. Our in vivo fluorescence technique is designed to allow real-time assessment of photosensitizer in tumor and normal tissues and therefore temporally optimal light delivery. Laser-induced fluorescence was used to measure photosensitizer concentration from multiple microscopic regions of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…14,[150][151][152] In vivo methods have also been utilized to directly measure the concentration of PS present in the tumour tissue, even though PS aggregation, photobleaching and tissue optical properties can ultimately confuse the issue. [153][154][155][156][157][158] Light delivery and penetration to the target tissue containing the accumulated PS is the next important step in the process. The wavelength of light used, as well as the optical properties of the tissue, will have a bearing on the PDT process.…”
Section: Pdt Dosimetrymentioning
confidence: 99%
“…14,[150][151][152] In vivo methods have also been utilized to directly measure the concentration of PS present in the tumour tissue, even though PS aggregation, photobleaching and tissue optical properties can ultimately confuse the issue. [153][154][155][156][157][158] Light delivery and penetration to the target tissue containing the accumulated PS is the next important step in the process. The wavelength of light used, as well as the optical properties of the tissue, will have a bearing on the PDT process.…”
Section: Pdt Dosimetrymentioning
confidence: 99%
“…Various concepts have been proposed for that purpose, ranging from tissue extraction [3] over fiber bundle probes [4,5] and ratioing techniques [6]. Recently, it has been suggested to use a single optical fiber for quantitative concentration measurements of fluor- [7].…”
Section: Introductionmentioning
confidence: 99%
“…2,4,9 Rather than using tissue-specific calibration curves, we have examined the use of a single calibration curve from tissue-simulating phantoms to perform quantitative fluorescence measurements in vivo. We have also considered the possibility that the fluorescence quantum yield of our model fluorophore may be different in vivo than in the tissue-simulating phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…Panjehpour et al 4 showed that sulphonated aluminum phthalocyanine fluorescence measured in rats depended linearly on concentration, which was determined by chemical extraction of tissue samples. A more recent study by Lee et al 9 compared measurements of AlPcS 2 concentration using a fiber bundle probe 10 to a chemical extraction technique. They used measurements of concentration in vivo to calibrate the probe, and used that calibration to quantify uptake in muscle and liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation